TI_GERICHTE 52.2019.87 vom 27. März 2015 , Posa di recinzioni nel bosco: licenza edilizia e permesso di dissodamento - TI Tribunale d'appello (2015)
Posa di recinzioni nel bosco: licenza edilizia e permesso di dissodamento